Welcome to the IALS Student Law Review - Lovina Otudor (IALS Student Law Review, 2019)
In this Editorial Lovina Otudor (Editor-in-Chief, ISLRev, Institute of Advanced Legal Studies) welcomes you to the Autumn 2019 issue of the IALS Student Law Review and introduces the articles featured in this issue of the journal.